Dukungan Keluarga Dan Lama Dialisis Sebagai Variabel Yang Berhubungan Dengan Kepatuhan Pembatasan Cairan Pasien Gagal Ginjal Kronik - tiurmaida simandalahi (Ners Jurnal Keperawatan, 2019)
Disobedience is a big problem, especially in patients undergoing hemodialysis. The Data of RISKESDAS in 2013, the patients  if Chronic Kidney Failure in Indonesian mencapai 30,7 million society. In West Sumatera as many as 368 patients.  The objective of the research to knows The Relationship of Family Support and Duration of Dialysis with Compliance with Liquid Restrictions in Patients with Chronic Kidney Failure (CRF) at RST Dr. Reksodiwiryo Padang in 2018. This type of research is descriptive analytic with cross sectional design. Data collection was conducted in August 2018 in the RST hemodialysis unit room Dr. Reksowidiryo Padang. The population in this study were all CRF patients who underwent hemodialysis therapy at RST Dr. Reksodiwiryo Padang, April to June 2018 with an average patient visit of 42 peoples. Sampling was done by total sampling as many as 42 people. Data were collected by questionnaire and documentation study on patients. Data has been collected manually and analyzed in univariate and bivariate. The results obtained 76.2% of patients did not adhere to the liquid limitation, 52.4% of patients get poor family support, 66.7% of patients undergoing hemodialysis have long dialysis There is a significant relationship between family support (p=0.030) and duration of dialysis (p=0.001) with compliance with fluid restriction at RST Dr. Reksodiwiryo Padang in 2018. It can be concluded that there is a relationship between family support and length of dialysis with adherence to fluid restriction in RST Dr. Reksodiwiryo Padang in 2018. It is recommended that officers handling patients undergoing hemodialysis pay more attention to the re-control schedule that has been determined on the control sheet, include and educate patients and families regarding fluid restriction, and provide alternatives that can be done for fluid replacement in controlling thirst. Keywords: Chronic Kidney Failure, Compliance with Liquid Restrictions, Duration of Dialysis, Family Support